ANALISIS DAMPAK KREDIT MIKRO TERHADAP PERKEMBANGAN USAHA MIKRO DI KOTA SEMARANG (Studi Kasus : Nasabah Koperasi Enkas Mulia) - Ayu Linda; Achma Hendra Setiawan (Universitas Diponegoro, 2012)
Micro, Small and Medium Enterprises (SMEs) sector is the largest growing economic sector in the field of trade and services. Generally, the problems faced by SMEs in Semarang is a matter of business, in which micro and small traders does not have enough capital to run and manage his business activities. The purpose of this study was to analyze the development of Micro Enterprises as well as the difference between before and after obtaining micro-credit the Enkas Mulia Cooperative in Semarang which include venture capital, labor (working hours), the turnover of sales and profits. Research object is the Micro Enterprises that become customers the Enkas Mulia Cooperative in Semarang with a sample of 70 respondents. Type of data collected are the primary data and secondary data. Data analysis methods used in this research include test validity, reliability test and wilcoxon sign rank test. Based on a wilcoxon sign rank test for variables obtained –p value of capital of 0.000 (0.000 < 0.05) which means there are different variables before and after obtaining micro-credit the Enkas Mulia Cooperative in Semarang or an increase of 108% of venture capital after getting micro-credit from the Enkas Mulia Cooperative in Semarang. For variable labor (working hours) obtained –p value of 0.000 (0.000 < 0.05) which means there are different variables before and after obtaining micro-credit from the Enkas Mulia Cooperative in Semarang or an increase in working hours by 12.5% after getting micro-credits from of the Enkas Mulia Cooperative in Semarang. Thus the presence of micro-credit the Enkas Mulia Cooperative in Semarang the could increase the variables business capital, labor (working hours), sales turnover and profit of Micro, Small and Medium Enterprises (SMEs) experienced significant improvement.